ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIK TOKO BANGUNAN UNTUK MENGAJUKAN PEMBIAYAAN DI BANK SYARIAH (Studi Pada Kecamatan Pamijahan dan Kecamatan Cibungbulang Kabupaten Bogor, Jawa Barat) - Nadia Febtianda; Rully Trihantana; Miftakhul Anwar (SAHID BANKING JOURNAL, 2021)
ABSTRACT The purpose of this study is to determine the factors that influence shop buildings in collecting financing at Islamic banks. This thesis is localized in promotion, confidence and environment. Respondents in this study were building shop owners. The sample used in this study were 30 respondents. The sampling technique used is non-probability sampling with purposive sampling method. The results of the T test concluded that trust (T count -2.710, sig. 0.038) and the environment (T count -2.185, sig. 0.012) influenced the building shop's decision to apply for financing, while promotion had no effect on buildings. the decision to apply for financing to Islamic banks because it has a T-value of -1.549 < T table +- 1.705 and sig. 0.133 > 0.05. Meanwhile, from the results of the research F table with a value of 4.115 and a significance value of 0.016 which is greater than F table of 2.98 and a significance value of 0.05 it can be concluded that promotion, self-confidence, and the environment together influence building decisions. apply for financing in Islamic banks. And the results of the study of the coefficient of determination concluded that the influence of promotion, trust, and the environment on the hardware store's decision to raise financing in Islamic banks was 22.4%.